Social Interaction Effects in Disability Pension Participation. Evidence from Plant Downsizing - Mari Rege; Kjetil Telle; Mark Votruba (Statistics Norway, Research Department, 2007)
We estimate the magnitude of social interaction effects in disability pension participation among older workers in Norway. Specifically, we investigate how a worker's propensity to draw disability benefits is affected by a plausibly exogenous shock to the disability entry rate of similarly-aged workers in his or her neighborhood. The problem of omitted variable bias is addressed by employing a novel instrumental variable (IV) strategy, using plant downsizing at neighbors' plants of employment as an instrument for the disability entry rate among one's previously employed neighbors. Our IV estimates suggest that a one percentage point increase in the participation rate of previously employed neighbors increased the subsequent 4-year entry rate of workers by about one-half a percentage point. Numerous robustness and specification tests appear to support the validity of the identifying assumption in our IV strategy.
Keywords: H55; I12; I38; J63; J65; 330; disability; downsizing; layoffs; plant closings; social insurance; social interaction; welfare norms